Morpho-physiological adaptations to drought stress in nitrogen-fixing and non-nitrogen-fixing plants - Zhao, Dongmin; Wei, Maohong; Wang, Xiaoting; Aqeel, Muhammad; Ran, Jinzhi; Deng, Jianming (Frontiers in Ecology and Evolution, 2024)
Drought profoundly affects the morpho-physiological responses of desert plants in dryland. To scrutinize the morpho-physiological responses of nitrogen (N)-fixing legumes (Ammopiptanthus mongolicus, Caragana korshinskii), N-fixing non-legumes (Elaeagnus angustifolia, Hippophae rhamnoides), and non-N-fixing plants (Nitraria tangutorum, Haloxylon ammodendron) under varied drought stress levels (75%, 50%, 25% and 5% of soil water holding capacity), a pot experiment was conducted in greenhouse. Following prolonged water deficit, carbon (C) and N stoichiometry, metabolic rates, plant growth, and biomass distribution of unstressed and stressed plants were recorded. Intensified drought significantly reduced stem, root and whole-plant biomass, with no significant changes observed in leaf dry-fresh mass ratio, specific leaf area, intrinsic water use efficiency and root to shoot ratio. However, other traits were impacted differently, reflecting distinct adaptive strategies to drought among three plant functional types (PFTs). Patterns of trait-soil water content (SWC) relationships varied across different PFTs, with N-fixing non-legumes followed by N-fixing legumes displayed greater sensitivity to SWC variations than non-N-fixing plants. This resulted in a shift from a stronger trait-SWC relationship in N-fixing non-legumes and N-fixing legumes to a less correlated relationship in non-N-fixing plants. The diverse responses to drought among PFTs suggest a shift from N limitation to water limitation as SWC decreases.